An analysis of the flight dynamics of a second generation SST aircraft - Steer, Anthony J. (Cranfield University, 1999)
This interim report covers an initial overview of delta-wing aircraft static, dynamic and control characteristics, collated from publications within the public domain and the authors related research. This is to give the reader an overall understanding how a delta-winged supersonic transport aircraft’ s characteristics differ to those of a conventional civil transport aircraft. This is followed by identifying the aircraft’s static and dynamic stability, with the effect of speed and CG location on the aircraft dynamic modes specifically addressed. Following this, a comprehensive investigation and analysis of the open loop response of a SCT baseline aircraft, in both low-speed cruise and approach and landing conditions, has been carried out. Both time and frequency domain techniques have been utilised. Finally, conclusions are made based on the results of the work presented.